2021
DOI: 10.1002/cpa.21988
|View full text |Cite
|
Sign up to set email alerts
|

Refined Description and Stability for Singular Solutions of the 2D Keller‐Segel System

Abstract: We construct solutions to the two‐dimensional parabolic‐elliptic Keller‐Segel model for chemotaxis that blow up in finite time T. The solution is decomposed as the sum of a stationary state concentrated at scale λ and of a perturbation. We rely on a detailed spectral analysis for the linearised dynamics in the parabolic neighbourhood of the singularity performed by the authors in [10], providing a refined expansion of the perturbation. Our main result is the construction of a stable dynamics in the full nonrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 70 publications
(84 reference statements)
3
24
0
1
Order By: Relevance
“…Finite time blow solutions had been predicted in [33], [7], [23]. Rigorous constructions were later done by Herrero-Velázquez, [19], [39], Raphaël-Schweyer [36] and the present authors [9] where the following blowup dynamics was confirmed:…”
Section: 1) {3dsys} {3dsys}supporting
confidence: 62%
See 2 more Smart Citations
“…Finite time blow solutions had been predicted in [33], [7], [23]. Rigorous constructions were later done by Herrero-Velázquez, [19], [39], Raphaël-Schweyer [36] and the present authors [9] where the following blowup dynamics was confirmed:…”
Section: 1) {3dsys} {3dsys}supporting
confidence: 62%
“…This blowup dynamics is stable and is believed to be generic thanks to the partial classification result of Mizoguchi [31] who proved that (1.4) is the only blowup mechanism that occurs among radial nonnegative solutions. Other blowup rates corresponding to unstable blowup dynamics were also obtained in [9] as a consequence of a detailed spectral analysis obtained in [8].…”
Section: 1) {3dsys} {3dsys}mentioning
confidence: 99%
See 1 more Smart Citation
“…This method has proved to be efficient for different PDEs from different types, and no list can be exhaustive (see del Pino, Musso and Wei [7], Nouaili and Zaag [32], Tayachi and Zaag [34], Duong and Zaag [8], Mahmoudi, Nouaili and Zaag [23], Merle, Raphael, Rodnianski and Szeftel [24], Collot, Ghoul, Nguyen and Masmoudi [6], etc...).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, a large literature has been devoted in the last 20 years to the construction of solutions of PDEs with prescribed behavior, beyond the case of parabolic equations such as: Type I anisotropic heat equation by Merle et al [51]; Type II blowup for heat equation by del Pino et al [21,22,23,24], Schweyer [65], Collot [13], Merle et al [12], Harada [33,34], Seki [66]; blowup for nonlinear Schrödinger equation by Merle [43], Martel and Merle [46], Merle et al [48,50,49], Raphaël and Szeftel [62]; Blowup for wave equations by Côte and Zaag [14], Ming et al [52], Collot [8], Hillairet and Raphaël [35], Krieger et al [41,40], Ghoul et al [30], Raphaël and Rodnianski [61], Donninger and Schörkhuber [25]; Blowup for KdV and gKdV [42], Côte [6,7]; Schrödinger map by Merle et al [47]; Heat flow map by Ghoul et al [31], Raphaël and Schweyer [64], Dávila et al [15]; Keller Segel system by Ghoul et al [10,11], Schweyer and Raphaël [63]; Prandtl's system by Collot et al [9]; Stefan problem by Hadzic and Raphaël [36]; 3-dimensional compressible fluids by Merle et al [49]; quenching phenomena for MEMS devices by Duong and Zaag [28]…”
Section: Introductionmentioning
confidence: 99%